2015
DOI: 10.1095/biolreprod.115.129759
|View full text |Cite
|
Sign up to set email alerts
|

Ghrelin Prevents Cisplatin-Induced Testicular Damage by Facilitating Repair of DNA Double Strand Breaks Through Activation of p53 in Mice1

Abstract: Cisplatin administration induces DNA damage resulting in germ cell apoptosis and subsequent testicular atrophy. Although 50 percent of male cancer patients receiving cisplatin-based chemotherapy develop long-term secondary infertility, medical treatment to prevent spermatogenic failure after chemotherapy is not available. Under normal conditions, testicular p53 promotes cell cycle arrest, which allows time for DNA repair and reshuffling during meiosis. However, its role in the setting of cisplatin-induced infe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 57 publications
1
16
0
Order By: Relevance
“…However, administration of ghrelin in mice treated with CP indicated that the ghrelin prevents the reduction in body weight and epididymis. In support of our findings, Garcia et al reported that ghrelin prevents decreased body weight and sexual organs of mice treated with cisplatin (Garcia et al, 2015). This protective effect of ghrelin could be attributed to the antioxidant activity of ghrelin under oxidative stress conditions.…”
Section: Discussionsupporting
confidence: 91%
“…However, administration of ghrelin in mice treated with CP indicated that the ghrelin prevents the reduction in body weight and epididymis. In support of our findings, Garcia et al reported that ghrelin prevents decreased body weight and sexual organs of mice treated with cisplatin (Garcia et al, 2015). This protective effect of ghrelin could be attributed to the antioxidant activity of ghrelin under oxidative stress conditions.…”
Section: Discussionsupporting
confidence: 91%
“…Our research focuses on developing adjuvants to preserve fertility in female cancer patients. Studies have shown that melatonin and ghrelin provide partial protection against cisplatin‐induced damage to the ovaries and testes . However, the administration of either drug alone does not provide adequate protection against cisplatin‐induced infertility and the effect of ghrelin on the ovaries remains uncharacterized.…”
Section: Introductionmentioning
confidence: 99%
“…Our results showed that CP treatment caused significant decrease in TTW, sperm motility, dead sperm rate, mid‐sperm abnormality, tail sperm abnormality and total sperm abnormality while only a numerical decrease in sperm cell density was observed when compared to control group. Our results were compatible with findings of several researchers (Ateşşahin et al ., ; Turk et al ., ; Rezvanfar et al ., ; Aksu et al ., ; Garcia et al ., ; Kaya et al ., ) and ratified the spermiotoxic effects of CP. RUT treatment mitigated some of mentioned spermatological parameters including sperm motility, dead sperm rate, mid‐sperm abnormality, tail sperm abnormality and total sperm abnormality.…”
Section: Discussionmentioning
confidence: 98%
“…To reduce side effects of the drug, usage of antioxidant compounds may be beneficial and important strategy for protecting of male fertility along chemotherapy period. CP treatment causes decrease in testis weight, sperm density, sperm motility, live sperm rate (Ateşşahin et al ., ; Turk et al ., ; Rezvanfar et al ., ; Aksu et al ., ; Garcia et al ., ), enzymatic or nonenzymatic antioxidant levels in testes (Ateşşahin et al ., ; Turk et al ., ; Rezvanfar et al ., ; Kaya et al ., ; Saral et al ., ) and degenerations in testicular tissue (Ateşşahin et al ., ; Turk et al ., ; Kaya et al ., ; Saral et al ., ). Although above‐mentioned researchers preferred different treatment procedures (as pre‐treatment, post‐treatment or combined treatment), we preferred pre‐treatment for 10 days and post‐treatment for 4 days with RUT from CP injection to avoid time‐dependent healing in studied parameters.…”
Section: Discussionmentioning
confidence: 99%